Jordan : Staff Report for the 2004 Article IV Consultation, Second Review under the Stand-By Arrangement, and Request for Waiver of Applicability. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the 2004 Article IV Consultation on Jordan highlights economic developments and policies. General sales tax collections increased strongly boosted by high import growth and improved revenue administration. The government has embarked on a substantial improvement of the education system, with support from an education sector reform loan from the World Bank. The integration of the sales and income tax departments into a unified revenue department will also contribute by strengthening tax collections and enforcement.